Some of these are snails - Higgins, Carter (Chronicle Books, 2023)
"From the creative force behind Circle Under Berry comes a deceptively simple picture book exploring sorting, comparatives, and quantifiers that teases the brain, twists expectations, and teaches basic ideas in unusual ways. A page-turner for first-time page-turners, this kaleidoscopic compendium shows young readers the infinite variability of perspective inherent in even our foundational concepts"--